How brand-cause fit shapes real world advertising messages: a qualitative exploration of 'femvertising'. Issue 8 (17th November 2019) - Champlin, Sara; Sterbenk, Yvette; Windels, Kasey; Poteet, Maddison
Abstract: Brand-cause fit, the concept that a brand and a social issue 'pair' together conceptually, has been a topic of great interest yet it is not fully understood due to inconsistent findings and limited theoretical development. In this study, we take a different approach to understanding brand-cause fit to explore how and in what ways 'fit' shapes advertising message strategies. A growing trend in advertising is 'brand responsibility', wherein a brand aligns itself with a social issue. A prominent focus of these messages is gender equality, namely, female empowerment. Advertisers utilize 'femvertisements' to emphasize their support of women. The motive behind this work is often called into question, given brands' inherent desire to sell products. Advertisers should consider how brands 'fit' with specific social issues. Through a qualitative analysis of advertisements that received an award for femvertising, this study sheds light on the differences in message themes between brands with high versus low brand-cause fit, specifically target audience brand-cause fit, in an effort to further this literature and advertising practice. Five key messaging themes are elucidated among high-fit brands (overt femininity, fixing the self, being a girl is a hardship, actors on set, and let's talk about it) and four themes among low-fit brands (low femininity, breaking stereotypes, reminders that women and men do the same activities, and getting men on board); which shape how women are depicted, the overall brand message, and the overall social issue message. Indeed, fit should be considered beyond simple high/low congruence. Implications for advertising practitioners and researchers are discussed.